Formulation of 5-fluorouracil Loaded Chitosan Nanoparticles By Emulsion Droplet Coalescence Method For Cancer Therapy - M, Anto Shering (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Nano technology is the one of the emerging field in the World also the Medical sciences. Since, it over come most of the disadvantages of conventional therapy. There are many products related to this technology is already marketed, and giving good results in patient compliance with related to side effects and sustained release. The goal of the present investigation was to formulate and evaluate nanoparticles of 5-Fluorouracil using Emulsion droplet coalescence method. In the present study we have taken chitosan, a natural marine polymer for the preparation of Nanoparticles. Eudragit S 100 was used to produce secondary coating upon the chitosan layer and drug used is 5-fluorouracil. Emulsion droplet coalescence method was used for the preparation. This formulation meant for IV use. So the pH maintained at 7.4. DSC graph shows that there is no interaction between Polymer and drug in the nanoparticles. Invitro diffusion study was carried out using Franz diffusion cell and the formulation CF 2 shows good encapsulation capacity, sustained drug release up to 12 Hours. The goal of the present investigation was to formulate and evaluate nanoparticles of 5-Fluorouracil using Emulsion droplet coalescence method.